‘There are no Victims Here’: Ethnography of a reintegration shelter for survivors of trafficking in Bangladesh - Bose, Diya (Anti-Trafficking Review, 2018)
This article, based on nine months of ethnographic data from a reintegration shelter for survivors of trafficking in Bangladesh, examines the tensions between claims of empowerment and the disempowering practices that undermine an organisation’s liberatory objective. The author documents how the leadership and other staff of an anti-trafficking NGO engage in regulating survivors’ desires, directing their desires by demanding that they perform a desire to engage in particular modes of self-improvement, and rehabilitating their desires to seek gender-conforming occupations. These three strategies together constitute disciplining desire, which I identify as a process of othering of poor Third World women and cultivating an ideal survivor subjectivity that conforms to gender and class expectations in the name of ‘reintegration’. This account encourages researchers to critically consider the micro-interactions that undermine the emancipatory goals within women’s empowerment regimes in the Global South.